Nature's Gift: Syzygium Aromaticum - Arzu Özgen; İlknur Yücel (Health and Technology Journal (HTechJ), 2024)
From ancient times to now, cloves have been utilized in traditional and culinary practices. Syzygium aromaticum, also known as clove, is extracted from the buds of a flowering plant that belongs to the Myrtaceae family. This oil comprises 85% Eugenol (4-allyl-2-methoxyphenol), 5.5% Eugenyl acetate, and 1.5% β-caryophyllene. S. aromaticum is known for its antibacterial, antiviral, antioxidant, and anti-inflammatory properties. S. aromaticum has multiple beneficial effects, including antifungal, antiemetic, antispasmodic, analgesic, antiseptic, anticarcinogenic, antiallergic, and anti-mutagenic activity. However, there is a lack of comprehensive information available in the current literature. To ensure the safe and effective use of clove oil, it is important for health professionals to receive adequate training through in-service programs, symposiums, conferences, and congresses. It is crucial to remember that clove oil contains powerful chemical compounds, and uncontrolled use may result in harm. Therefore, it should only be used under the supervision of a health team. It is recommended to raise public awareness about the proper use of clove oil by health professionals.